DNA sequence variation in the promoter region of the VEGF gene impacts VEGF gene expression and maximal oxygen consumption - Prior, Steven J; Hagberg, James M; Paton, Chad M; Douglass, Larry W; Brown, Michael D; McLenithan, John C; Roth, Stephen M (American journal of physiology. Heart and circulatory physiology, 2006)
Departments of 1 Kinesiology and of 2 Animal and Avian Sciences, University of Maryland, College Park; and 3 Division of Endocrinology, Diabetes, and Nutrition, University of Maryland School of Medicine, Baltimore, Maryland Submitted 29 September 2005 ; accepted in final form 29 November 2005 In its role as an endothelial cell proliferation and migration factor, vascular endothelial growth factor (VEGF) can affect peripheral circulation and therefore impact maximal oxygen consumption ( O 2 max ). Because of the role of VEGF, and because variation in the VEGF gene has the ability to alter VEGF gene expression and VEGF protein level, we hypothesized that VEGF gene polymorphisms are related to VEGF gene expression in human myoblasts and O 2 max before and after aerobic exercise training. We analyzed the effects of the VEGF 2578/1154/634 promoter region haplotype on VEGF gene expression by using a luciferase reporter assay in cultured human myoblasts and found that the AAG and CGC haplotypes resulted in significantly higher hypoxia-stimulated VEGF gene expression than the AGG and CGG haplotypes. Consistent with these results, we found that individuals with at least one copy of the AAG or CGC haplotype had higher O 2 max before and after aerobic exercise training than did subjects with only the AGG and/or CGG haplotype. In conclusion, we found that VEGF 2578/1154/634 haplotype impacts VEGF gene expression in human myoblasts and is associated with O 2 max . These results have potential implications for aerobic exercise training and may prove relevant in the study of pathological conditions that can be affected by angiogenesis, such as coronary artery disease and peripheral artery disease. angiogenesis; exercise; genetics; polymorphism Address for reprint requests and other correspondence: S. J. Prior, Baltimore Veterans Affairs Medical Center, Geriatrics (18), Rm. 4B-205, 10 N. Greene St., Baltimore, MD 21201 (e-mail: sprioratgrecc.umaryland.edu )